KAJIAN EMPIRIS INTERNET FINANCIAL REPORTING DAN PRAKTEK PENGUNGKAPAN - Reskino ,; Nova Ninda Jufrida Sinaga (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2016)
Purpose – Internet is a medium with applications that are used to streamline the communication process including the communication of financial statements to the parties concerned. This study examined the factors that affect the company's financial reporting on the internet property sector, real estate and building construction. These factors include firm size, leverage, profitability and liquidity of the financial reporting through the internet (IFR).Design/methodology/approach – Secondarydata were sourced from 53 samples of the company which listed in the Indonesia Stock Exchange in 2013. The study was conducted on Research data analysis using logistic regression analysis with dummy variables and t test (partial) with significance level of 5%.Findings –The analysis found that only the size of companies that have effect on the financial reporting through the internet (internet financial reporting). However leverage, profitability, and liquidity do not explain the company choice to use IFR.Originalitas – This is one of the studies to examine the factors that influence the disclosure of financial statements on the Internet at property sector, real estate and building construction. The artikel provides a valuable contribution to researchers and practitioners to extends the understanding of IFR at property sector, real estate and building construction Keywords: Internet Financial Reporting, Firm Size, Leverage, Profitability, Liquidity, Voluntary Disclosure